Sistemas compuestos FRCM a base de tejidos de fibras de cabuya y vidrio para el fortalecimiento de columnas y vigas de concreto reforzado - Pazmiño Cepeda, Marcela Alejandra (2017)
Reinforced concrete structures must have an appropiate useful life, and could be assumed that the initial design requirements and considerations must take into account several factors such as durability and the presence of natural phenomena. Now days, the repair and reinforcement of structures is a daily activity in civil engineering, with the purpose of not leaving abandoned or demolishing buildings with structural problems. For this reason, strenthening systems are increasingly being studied, and among these systems, the FRCM (Fabric Reinforced Cementitious Matrix) composites produced using synthetic or natural fiber fabrics are a viable option to repair or reinforce various types of structures. In this study, FRCM systems based on sisal and glass fiber fabrics were designed. For glass, these fabrics are comercialized in Ecuador and Colombia to be used primarily in the manufacture of gasoline tanks and have not been used in the construction industry, even more in the production FRCM composites. An advantage of these glass fabrics, compared to the glass fabrics traditionally used in the construction industry, is their economy. The main physical and mechanical characteristics of the composites considered in this study were evaluated. After carrying out the characterization and determining how many layers of reinforcing fabrics are going to be used, we proceeded to build scale models of structural elements of reinforced concrete beams and columns to perform four point flexural tests and concentric compression tests, respectively. In this way, properties such as strength capacity, deformability and ductility were studied. In the case of beams and columns without FRCM reinforcement, these samples evidently obtained lower strengths than those reinforced with FRCM systems. FRCM-reinforced beams based on woven sisal fabrics reached a flexural strength of 14,591 MPa and FRCM-reinforced beams based on glass fabrics reached a flexural strength of 20,875 MPa, compared to 11,310 MPa obtained by the beams without FRCM reinforcement. On the other hand, the columns without reinforcement of FRCM composites reached a compressive strength of 17,281 MPa, a result much lower than those obtained in the case of columns reinforced with FRCM systems based on sisal (33,723 MPa) and glass (34,456 MPa). These encouraging results demonstrate the potential of the FRCM systems designed in this study for the structural strengthening of reinforced concrete elements. Additionally, in this investigation, a numerical analysis of the behavior of the reinforced concrete elements strengthened with FRCM composite materials subjected to flexion and compression was performed, and the results were compared with those experimentally obtained from the samples built and reinforced with the considered FRCM systems in the Laboratory of Quality Control of Materials of the UNACH.